2012
DOI: 10.1179/1743284712y.0000000021
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of constitutive behaviour of 20CrMnTiH steel under hot deformation conditions

Abstract: Isothermal compression tests are carried out on 20CrMnTiH steel using a Gleeble-1500 thermal simulator in the temperature range of 1223–1423 K and in the strain rate range of 0·01–10 s−1. The flow behaviours of 20CrMnTiH steel are described, which are based on the analysis of true stress–true strain curves. The effects of hot deformation on the microstructure are investigated. The results show that there is a typical dynamic recrystallisation behaviour during deformation. A constitutive model coupling flow str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…There are diverse thermomechanical deformation data on steels 15,[19][20][21][22][23][24][25][26][27] and other alloys [28][29][30][31] available in the relevant technical literature, none of which is on steel grade DH36 and in conditions that simulate FSW. One publication 15 discusses the effect of temperature and strain rate on the high temperature (850-1150uC) deformation behaviour of 42CrMo medium carbon low alloy steel by hot compression testing on a Gleeble thermomechanical simulator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are diverse thermomechanical deformation data on steels 15,[19][20][21][22][23][24][25][26][27] and other alloys [28][29][30][31] available in the relevant technical literature, none of which is on steel grade DH36 and in conditions that simulate FSW. One publication 15 discusses the effect of temperature and strain rate on the high temperature (850-1150uC) deformation behaviour of 42CrMo medium carbon low alloy steel by hot compression testing on a Gleeble thermomechanical simulator.…”
Section: Introductionmentioning
confidence: 99%
“…There are diverse thermo-mechanical deformation data on steels 15,[19][20][21][22][23][24][25][26][27] and other alloys [28][29][30][31] C) deformation behaviour of 42CrMo medium carbon low alloy steel by hot compression testing on a Gleeble thermo-mechanical simulator. It is reported that in high temperature and low strain rate deformation conditions, flow stress curves consist of four diverse stages which are governed by two opposing phenomena, work hardening and thermally induced softening, specifically dynamic recrystallisation (DRX) and dynamic recovery (DRV).…”
mentioning
confidence: 99%
“…The Arrhenius equation is used to solve the activation energy [4,6], and the relationship of flow stress and deformation conditions can be obtained for different stress level, as follows:…”
Section: Z Parameter Effect On Recrystallised Microstructure and Vick...mentioning
confidence: 99%
“…Chai et al proposed a modified Zerilli-Armstrong (ZA) model based upon the original ZA model and Johnson-Cook model to describe the flow stress under different deformation conditions and analysed the dynamic softening features during warm forming 20CrMnTiH steel [5]. Besides, Chai et al investigated the deformation behaviour and proposed a constitutive equation coupling flow stress with strain, strain rate and temperature using a hyperbolic sine equation during hot forming 20CrMnTiH steel [6]. Wu et al investigated the rules of the plastic deformation behaviour based on the experimental results, and the thermoplastic constitutive model of 20CrMnTiH steel with a modified Zener-Hollomon parameter was proposed based on the Arrhenius equation, which provides the basic of numerical simulation of 20CrMnTiH steel forging process [7].…”
Section: Introductionmentioning
confidence: 99%
“…But, the PM high-speed steel is relatively less investigated. In the deformation process, constitutive equation as an important part of hot deformation has been researched in a great number of steels and alloys [5][6][7][8][9][10][11][12][13][14][15][16] . Constitutive equation can be used to describe the relationship of deformation temperature, true strain, strain rate and flow stress.…”
Section: Introductionmentioning
confidence: 99%